Comparative characteristics of extended endoscopic endonasal operations in giant pituitary adenomas with ventricular system extention and craniopharyngiomas - A.A. Chukov; O.V. Ukrainets (Українська Інтервенційна Нейрорадіологія та Хірургія, 2023)
Objective ‒ to evaluate the results of extended endonasal interventions in patients with craniopharyngioma (CPH) and giant pituitary adenoma (GPA) with an extension to ventricular system, to compare the effects of interventions in these pathologies, to determine the basic principles of extended endoscopic endonasal surgical interventions. Materials and methods. The study is based on a retrospective analysis of patients endoscopically operated through the nose in the Department of Endonasal Neurosurgery of the Skull base in the SI «Romodanov Neurosurgery Institute NAMS of Ukraine» from 2014 to 2021. In the group with GPA were 18 (36.7 %) female and 31 (63.3 %) male patients. The mean age of the patients was 54.1±11.3 years. The CPH group included 42 (60.9 %) women and 27 (39.1 %) men. The mean age in this group was 46.6±14.5 years. Results. In 14.3 % of GPA cases, postoperative cerebrospinal fluid leak (CSFL) occurred, which is statistically insignificant compared to the postoperative CSFL level at CPH – 13 %, despite the fact that when removing GPA, we routinely encountered high-flow liquorrhea, given the characteristics of tumor growth (p=0.921). The number of electrolyte abnormalities with CPH was higher than with GPA removal (40.5 % with CPH versus 16.3 % with GPA). For the first time, diabetes insipidus requiring the prescription of hormone replacement therapy due to the removal of GPA that were extending to the ventricular system was diagnosed in the postoperative period in 12.2 % of patients versus 33.3 % in CPH group. Endocrine disorders in the form of hypopituitarism were found in 34.7 % of GPA and 44.9 % of CPH. The median duration of the operation was 227.9±74.9 min for GPA and 318.4±65.4 min for CPH. The area of the trepanation window is always larger in GPA, as it includes an enlarged sellar window and, sometimes, a parasellar direction in the invasion of the cavernous sinuses. Decompression of the optic canals was performed almost exclusively in GPA that extend parasellarly and/or retrosellarly (38,0 % with CPH in comparison to 5.8 % in the GPA group). Closure of the skull base defect was performed with autologous and artificial materials in all cases, as the removal of GPA and CРН was always accompanied by high-flow intraoperative CSFL. Conclusions. After analyzing the results of endonasal surgeries performed in GPA with extension to the ventricular system and CPH, it was noted that the use of extended transtuberculum-transplanum approach provides a wide surgical corridor and provides the possibility of total tumor removal. It is essential to install a lumbar drainage system when working in open liquid spaces. In our opinion, the priority should be given to the safety of operations and prevention of postoperative interventions (preservation of the pituitary stem, perforating arteries, chiasm, minimization of manipulations with the diencephalic areas and the bottom of the III ventricle), rather than increasing radicality in CPH, as in GPA. Fatty graft packaging should be avoided for CPH located near the junction of the optic nerves (in the anterior position of the chiasm), as the absence of the arachnoid barrier increases the risk of involving the optic structures in the postoperative scar.